Effects of different transcranial magnetic stimulations on neuropathic pain after spinal cord injury - Yang, Chuanmei; Bi, Yunfeng; Hu, Luoman; Gong, Lili; Li, Zhanfei; Zhang, Nanyang; Wang, Qiang; Li, Jiang (Frontiers in Neurology, 2023)
Introduction Repetitive transcranial magnetic stimulation (rTMS) is an effective non-invasive cortical stimulation technique in the treatment of neuropathic pain. As a new rTMS technique, intermittent theta burst stimulation (iTBS) is also effective at relieving pain. We aimed to establish the pain-relieving effectiveness of different modalities on neuropathic pain. The study was conducted in individuals with spinal cord injury (SCI) and different modalities of rTMS. Methods Thirty-seven individuals with SCI were randomly allocated to three groups, in which the “iTBS” group received iTBS, the “rTMS” group received 10 Hz rTMS, and the “iTBS + rTMS” group received iTBS and 10 Hz rTMS successively of the primary motor cortex 5 days a week for 4 weeks, and they all underwent the full procedures. The primary outcome measure was change in the visual analog scale (VAS), and the secondary outcomes were measured using the Hamilton Rating Scale for Depression (HAM-D) and the Pittsburgh Sleep Quality Index (PSQI). All the outcomes were evaluated at 1 day before stimulation (baseline), 1 day after the first week of stimulation (S1), and 1 day after the last stimulation (S2). Results The VAS scores showed significant pain improvement after 4 weeks of stimulation (p = 0.0396, p = 0.0396, and p = 0.0309, respectively) but not after 1 week of stimulation. HAM-D scores declined, but the decreases were not significant until 4 weeks later (p = 0.0444, p = 0.0315, and p = 0.0447, respectively). PSQI scores were also significantly decreased after 4 weeks of stimulation (p = 0.0446, p = 0.0244, and p = 0.0088, respectively). Comparing the three modalities, VAS, HAM-D, and PSQI scores at S1 showed no differences, and, at S2, VAS scores showed significant differences (p = 0.0120; multiple comparisons showed significant differences between iTBS and iTBS + rTMS, p = 0.0091), while the HAM-D and PSQI scores showed no differences. Discussion The primary and secondary outcomes all showed significant improvement, indicating that the three different modalities were all effective at relieving the pain. However, not all the three stimulations were of same effectiveness after treatment; there were statistical differences in the treatment of neuropathic pain between iTBS as a priming stimulus and as a single procedure.